Sedentary Screen Time and Health-related Outcomes among Female Workers at North Aceh Government Office - Sawitri, Harvina; Maulina, Nora; Rahayu, Mulyati Sri; Nadira, Cut Sidrah; Yuziani, Yuziani (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
A significant segment of the global labor force dedicates a significant portion of their working days to office environments, where they typically engage in sedentary activities such as using computers. An office worker's typical workday consists of more than six hours spent sitting down to play games on their smartphones or watch videos. During the workday, women sat for over six hours a day. The risk of all-cause mortality from cancer, coronary heart disease (CHD), and cardiovascular disease (CVD) was higher in women who reported the highest levels of sedentary behavior. This study aimed to assess the level of sedentary screen time in women and its association with health problems. A cross-sectional study was conducted among 115 female workers at the North Aceh Government Office from July 2023 to February 2024. Data were collected through face-to-face interviews using screen-time questionnaires and direct measures. Pearson correlation and independent t-tests were used to assess the correlation between screen time and health problems. Linear regression was used to see which variables were most related. The result shows that most female workers were young, civil servants, had grade 1 hypertension (35.7%) and were overweight (53%). Average screen use on a weekday is 476.87 minutes, average screen use on a weeknight is 194.61 minutes, and average screen use on a weekend is 491.48 minutes. Screen use on weekdays and weeknights can be potential predictors for BMI, and screen use on weekdays and weekends can be potential predictors for hypertension.